(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background- Virtual reality (VR) is an effective drug-free tool for management of pain. However, its use remains elusive in developing countries like Nigeria. Objectives: To characterize studies conducted on using virtual reality in managing pain. Methods: A comprehensive systematic review was conducted for studies done globally from 2000 to 2016. Databases (Google, Pubmed, BioMed Central, Mendeley) were searched to identify eligible studies. Search terms included: Virtual reality, Virtual patients, and management of pain using VR. Data extracted included: Title/authors of articles, objectives, study design, methods, population, age group, primary disease conditions, VR equipment, environments, display technology/ senses needed, country of study, effect of VR plus pharmacologic analgesia, and study outcomes. Results: Out of 3821 potentially relevant articles identified 24(0.63%) were eligible. Fourteen (58.3%) and 8(33.3%) studies were Randomized Control Trials, and Case Studies/Reports respectively. A total of 8(33.3%) and 3(12.5%) studies were on Burn pain and Phantom limb pain respectively. Seventeen (70.8%) studies had adults as target population. Thirteen (54.2%) studies were done in the USA, 19 (79.2%) were Immersive VR, 15(62.5%) had head mounted display as display technology, and 22 (91.67%) had positive outcomes. VR plus pharmacologic analgesia 8 (33.37%) had positive outcomes. No study was found for Nigeria. Conclusion: This review demonstrates wide range of characteristics for studies encountered and VR is shown as effective for reducing pain in different disease conditions even when combined with pharmacological analgesia. The absence of studies on management of pain using VR in Nigeria calls for creation of awareness among major stakeholders.